ATTITUDES, PROBLEMS, AND FACTORS INFLUENCING THE USE OF E-LEARNING (LEARNING MANAGEMENT SYSTEM) AT IAIN ANTASARI - Raida Asfihana; Yansyah Yansyah (Universitas Potensi Utama, 2018)
The demand for integrating e-learning with face-to-face classroom is not merely a recommendation but now it becomes a necessary to be applied by higher education institutions. IAIN Antasari as one of higher institutions in South Kalimantan applied Learning Management System (LMS) to answer this demand. This research then tried to map the lecturers’ attitudes, problems, and individual factors of the lecturers that influences their attitudes toward this e-learning application. This study used cross sectional survey design by inviting 35 lecturers as the samples. Questionnaire and interview were utilized to gather the data. The findings showed that most of lecturers at IAIN Antasari had positive attitudes toward the application of the LMS. However, it also found that those lecturers had some barriers to apply the LMS, including their insufficient skills and knowledge, lack of facilities, lack of practice in the LMS training, lack of support from the head of faculty, lack of time for preparing the LMS materials, and negative influence from their colleagues. Regarding the factors influencing the lecturers attitudes for using the LMS, there was only ages variable which statistically significantly influencing.